Peningkatkan Pertumbuhan dan Produksi Tanaman Padi Gogo Varietas Dayang Rindu melalui Aplikasi Vermikompos - Safriyani, Etty; Sumini, Sumini; Holidi, Holidi; Nisa, Dinda Khairun (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Safriyani E, Sumini S, Holidi H, Nisa DK. 2022. The growth and production increment of rice upland dayang rindu variety through vermicompost application. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 136-142. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Vermicompost is an organic fertilizer that can improve soil physical properties including structure, porosity, soil permeability and improve soil chemical properties because it contains macro and micro nutrients. This study aimed to examine the role of vermicompost in increasing the growth and production of upland rice plants of Dayang Rindu variety. This research was conducted in Musi Rawas Regency at an altitude of 103 meter above sea level, from February to June 2021. The study used an experimental method with a non-factorial Randomized Block Design (RBD) with 5 treatments and 5 replications, namely (V0) without vermicompost/control, (V1) 22.5 grams/polybag, (V2) 45 grams/polybag, (V3) 67.5 grams/polybag, (V4) 90 grams/polybag. The observed variables included plant height, total tillers, number of panicles per clump, production per clump, weight of 1000 grains, root length and root weight. The data was analyzed used analyses of variance and Tukey’s honestly significant different test. The results showed that the application of vermicompost can increase the growth and production of upland rice plants of the Dayang Rindu variety. The vermicompost treatment of 90 grams/polybag resulted in the best growth and production of upland rice plants.